2018
DOI: 10.1007/s00213-018-5134-y
|View full text |Cite
|
Sign up to set email alerts
|

An experimental medicine study of the phosphodiesterase-4 inhibitor, roflumilast, on working memory-related brain activity and episodic memory in schizophrenia patients

Abstract: Rationale Schizophrenia is associated with impairments in cognitive functioning yet there are no approved drugs to treat these deficits. Objectives Based on animal models, we investigated the potential for roflumilast, a selective inhibitor of phosphodiesterase type 4 (PDE4), to improve cognition, which may act by increasing intracellular cyclic adenosine monophosphate in brain regions underlying cognitive deficits in schizophrenia. Methods This study consisted of a randomised, double-blind, placebo-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…Roflumilast has also been tested for its ability to improve cognition and information processing in healthy humans, with promising results observed at a dose previously indicated as being devoid of side effects (125). Patients with stabilized schizophrenia receiving adjuvant roflumilast in a small Phase II trial showed no improvement in working memory but did show some improvement in verbal learning and memory (126). Given these positive findings, roflumilast was tested in elderly subjects who demonstrated no change in spatial memory but improved verbal word memory with roflumilast treatment (127).…”
Section: Pde4 Inhibitorsmentioning
confidence: 99%
“…Roflumilast has also been tested for its ability to improve cognition and information processing in healthy humans, with promising results observed at a dose previously indicated as being devoid of side effects (125). Patients with stabilized schizophrenia receiving adjuvant roflumilast in a small Phase II trial showed no improvement in working memory but did show some improvement in verbal learning and memory (126). Given these positive findings, roflumilast was tested in elderly subjects who demonstrated no change in spatial memory but improved verbal word memory with roflumilast treatment (127).…”
Section: Pde4 Inhibitorsmentioning
confidence: 99%
“…Cognitive enhancement in humans is scarcely achieved, however, it has been noted with the PDE4 inhibitor roflumilast in several preclinical trials, establishing proof of concept that PDE4 is a therapeutic target for AD [10,11]. The potential effects of these inhibitors are attributed to the widely recognized action of cAMP on memory formation [12,13] and cognition [10,11,14,15]. The mechanisms underpinning these functions relate to intracellular increases in cerebral cAMP that activate PKA associated with cAMP response element binding (CREB) protein.…”
Section: Pde4 Enzymes Orchestrate Signaling Via Crebmentioning
confidence: 99%
“…PDE4 may be particularly relevant for the treatment of schizophrenia, because it regulates cAMP levels in the axon terminal afferents to the striatum (Heckman et al, 2016). Evidence has been accumulating to indicate that PDE4 inhibitors can remediate cognitive deficits, particularly memory deficits in animals (Barad et al, 1998; Hosseini-Sharifabad et al, 2012; Vanmierlo et al, 2016) including in primates (Rutten et al, 2008) in a rodent model of psychosis (Wiescholleck and Manahan-Vaughan, 2012) and most recently in patients with schizophrenia (Gilleen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%